PENGARUH HARGA DAN KUALITAS PRODUK KOSMETIK PEMUTIH WAJAH TERHADAP MINAT BELI SISWI SMA NEGERI 1 2X11 ENAM LINGKUNG - Ulfa, Annisa (journal of residu, 2019)
Cosmetics that are widely used by Indonesian women are bleaching cream products, known as whitening creams. Bleach cosmetics on the face is an ingredient that is used to brighten or change unwanted skin color, facial whitening cosmetics that are circulating in the market contain many dangerous ingredients (illegal). This study aims to a) determine the effect of face whitening cosmetics prices on student buying interest, b) determine the effect of quality face whitening cosmetic products on high school students' buying interest, c) determine the effect of price and quality of facial whitening cosmetic products on the buying interest of female high school students 1 2x11 Six Circles. This research was conducted at SMA Negeri 1 2x11 Enam Lingkung in October 2019. The population in this study were all students of the 2019/2020 school year as many as 100 students. Data analysis techniques using multiple linear regression test. Based on the results of the study note the coefficient value of 0.130 and the value of t count> t table is 2.139> 1.984, meaning that the hypothesis Ha is accepted and there is an influence of the price of facial whitening cosmetics on buying interest, the coefficient value of 0.101 and the value of t count> t table is 4.233> 1.984 means the hypothesis Ha is accepted and there is an influence of the quality of facial whitening cosmetic products on the buying interest of SMA Negeri 1 2x11 Six Lingkung students and there is an effect of price and product quality together on student buying interest with a calculated F value> F table that is 14.353> 3.94, meaning that Ha's hypothesis is accepted. It is recommended for school principals to provide education and socialization about the chemical content of illegal whitening cosmetics and their impact on facial skin, so students get a picture of the dangers of using the bleach complex.